لأصوات العربية: دراسة وصفية في علم الأصوات الحديث: Arabic Morphology, A descriptive Study - Umar Yunus, Sa’idu (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
ملخص: يبرز أهمية هذه الورقة مما تلعب الصوائت دورا كبيرا في التمييز بين اللغات، فهي التي تحدد طبيعة أي لغة من حيث نطقها وتركيبها ثم إن اختلافها من لغة إلى أخرى يجعل النطق بها من قبل أجنبيّ شاقا مسبرا لصعوبة وصفها، على خلاف الصوامت التي يشترك في نطقها كثيرا من اللغات. لهذه العوامل وغيرها جعلت العلماء والباحثين مجتهدون في الاستنباط مقايس عامّة تقاس بها كلّ لغة وتنسب إليها. وتتميّز الصّوائت بالوضوح السمعي وقوّة الرنين؛ ذلك لأنها مجهورة وهذا ما يجعلها أكثر دورانا على اللسان. وتوجد في العربية ستة فسنيمات من الصوائت بتغيرها بتغير المعنى هي: الفتحة والفتحة الطويلة والكسرة والكسرة الطويلة؛ والضمة والضمة الطويلة، تتنوع في السياقات اللغوية إلى ألوان مختلفة لا تؤدي إلى تغيير الدلالة كالإمالة والتفخيم. Abstract Arabic Grammarians have worked on major phonetical as well as phonological aspects of Arabic production points. The vocalic points are relatively not attended to in most these studies. This paper thus seeks to examine the various acts of vowels production with particular reference to Modern Standard Arabic Phonology. It employs analytical and descriptive methods. This is done by presenting an overview of the places of articulation of the vowels alongside their descriptive characteristics. Voiced and voiceless. The variety of the pronunciation contexts in terms of both high and low positions are examined with the level of its audibility and emphasis are all encapsulated in this work. The study conclusively espoused the difficulty in the pronunciation of some Arabic letters with illustrated examples for further reading.